The growing burden of overweight and obesity in contemporary China - Wu, Y.; Huxley, Rachel; Li, M.; Ma, J. (2009)
Once considered to have one of the leanest populations, China is fast catching up with the West. Recent estimates from the 2002 China Health and Nutrition Survey indicate that nearly 215 million Chinese are affected, about 22% of adults, 5% of children ages 0-6 years and 7% of those ages 7-17 years. Although the prevalence of overweight and obesity in China is relatively low compared with countries in the West, it is the rate of increase that gives the greatest cause for concern. From 1992 to 2002 the prevalence of adult overweight increased by nearly 40% and that of obesity doubled. Particularly among rural Chinese who account for more than 60% of the country's total population, the prevalence, although significantly lower than that found in urban areas, has increased two to three-fold over the 10 year time period. Studies suggest that changes to the traditional diet, reduced levels of physical activity, increased sedentary lifestyles, lack of health knowledge on obesity, and traditional social attitudes towards body fatness are major drivers of the increasing trend. Improving the level of awareness about the hazards associated with excess weight through wide-reaching health education campaigns is a fundamental first step in combating the epidemic. Actions have been undertaken by the government, some academic societies and experts. National and regional programs focusing on health education and school children have been initiated, However, potential solutions to China's obesity crisis are still for the most part theoretical, and it will be many years before the efficacy of the current strategies that have been initiated can be evaluated. Crown Copyright © 2008.